2018
DOI: 10.1021/acs.chemrestox.8b00244
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of 8-Oxo-7,8-dihydro-2′-deoxyguanosine Leads to Substantial DNA-Histone Cross-Links within Nucleosome Core Particles

Abstract: 8-Oxo-7,8-dihydro-2’-deoxyguanosine (8-oxodGuo) is a common primary product of cellular oxidative DNA damage. 8-OxodGuo is more readily oxidized than 2’-deoxyguanosine (dG); a two-electron oxidation generates a highly reactive intermediate (OGox), which forms covalent adducts with nucleophiles, including OH−, free amines, and the side chains of amino acids such as lysine. We determined here that K3Fe(CN)6 oxidation of 8-oxodGuo in nucleosome core particles (NCPs) produces high yields, quantitative (i.e. 100%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…13 The low levels of the hydantoin lesions in cellular environment can be associated with the competitive formation of other oxidation products, 14 including crosslinks between 8-oxoG and histones in nucleosomes in relatively high yields. 15 Although the cellular levels of hydantoin lesions are low, they can contribute to the malignant transformation of cells because they are at least one order of magnitude more mutagenic than 8-oxoG. 16 Recent observations suggest that the hydantoin lesions are not only excellent BER substrates, [17][18][19][20][21] but are also excised by the NER pathway in human cell-free extract.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The low levels of the hydantoin lesions in cellular environment can be associated with the competitive formation of other oxidation products, 14 including crosslinks between 8-oxoG and histones in nucleosomes in relatively high yields. 15 Although the cellular levels of hydantoin lesions are low, they can contribute to the malignant transformation of cells because they are at least one order of magnitude more mutagenic than 8-oxoG. 16 Recent observations suggest that the hydantoin lesions are not only excellent BER substrates, [17][18][19][20][21] but are also excised by the NER pathway in human cell-free extract.…”
Section: Introductionmentioning
confidence: 99%
“…Existing paradigms suggest that nonbulky oxidatively generated DNA lesions are removed by base excision repair (BER) mechanisms, while bulky DNA double helix-distorting lesions are excised by the nucleotide excision repair (NER) pathway. For example, DNA lesions such as oxidatively generated 8-oxo-7,8-dihydroguanine (8-oxoG) are known to be substrates of BER only. The 8-oxoG lesions are more easily oxidized than the parent base guanine, and their oxidation can lead to the formation of stereoisomeric spiroiminodihydantoin (Sp) and 5-guanidinohydantoin (Gh) lesions. The accumulation of Sp lesions was detected in Nei-deficient Escherichia coli cells treated with chromate and were also detected in both the liver and colon tissues of Rag 2 –/– mice at levels ∼100 times lower than those of 8-oxoG . The low levels of the hydantoin lesions in cellular environment can be associated with the competitive formation of other oxidation products, including cross-links between 8-oxoG and histones in nucleosomes in relatively high yields . Although the cellular levels of hydantoin lesions are low, they can contribute to the malignant transformation of cells because they are at least 1 order of magnitude more mutagenic than 8-oxoG …”
Section: Introductionmentioning
confidence: 99%
“…The dsDNA sequence used in this study was 145 bp ‘601’ DNA, which forms stable, well-positioned NCPs ( 26 , 27 ). Following the procedure we reported previously ( 23 ), we prepared free dsDNA and NCPs containing a single 8-oxodGuo/C base pair at each of positions 73, 89 and 137 (Figure 2A ). To facilitate subsequent gel imaging, we labelled the 8-oxodGuo-modified strand with a 5′-FAM group.…”
Section: Resultsmentioning
confidence: 99%
“…dsDNA and NCPs containing a single 8-oxodGuo/C base pair (referred to as dsDNA-8-oxodGuo and NCP-8-oxodGuo, respectively) at three different positions (73, 89 and 137) were prepared according to the procedure we reported previously ( 23 ). dsDNA and NCPs containing a single AP at position 137 (referred to as dsDNA-AP 137 and NCP-AP 137 , respectively) were obtained by in situ photolysis of dsDNA and NCPs containing a photoprotected AP 137 ( 21 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, the increased electrophilicity of the C5 position makes 8-oxo-dG suitable for reaction with the amino groups of proteins (e.g., lysine lateral chains), leading to the formation of irreversible protein–DNA CL adducts [ 63 ]. Using histone mutants, Bai et al demonstrated that G-oxidation can, in some cases, produce quantitative DNA–protein adducts in nucleosome-core particles [ 64 ]. Although underestimated, this type of lesion can have deleterious consequences for the normal DNA biology, as it can disrupt the normal disposition of the double helix, blocking the transcription and replication of the DNA and limiting the repair mechanisms [ 65 ].…”
Section: Reaction Of Singlet Oxygen With Biomoleculesmentioning
confidence: 99%